ANALYSIS OF THE EFFECT OF ELECTRODE TYPE VARIATION AND PWHT TEMPERATURE VARIATION ON SMAW WELDING ON THE IMPACT STRENGTH AND BENDING OF ST 42 STEEL - Muhammad agung nadjmi nasution; Kisto (Magister Teknik Mesin Universitas Pancasila, 2026)
ST 42 steel is a medium carbon steel that is widely used in the construction and shipping industries because it has high strength and ability to accept heat treatment. However, the welding process using the Shielded Metal Arc Welding (SMAW) method often causes residual stress that can reduce the quality of the weld joint. To overcome this, Post Weld Heat Treatment (PWHT) is needed to reduce residual stress, refine the microstructure, and improve the mechanical properties of the weld. This study aims to analyze the effect of variations in electrode types (E7016 and E7018) and PWHT temperatures (500°C and 600°C) on the flexural strength and toughness of ST 42 steel weld joints. The welding process was carried out at position 1G, then the specimen was given PWHT for 60 minutes. Testing was carried out using a bending test to assess flexural strength and an impact test to measure the toughness of the joint. The results showed that PWHT had a significant effect on improving mechanical properties. In the bending test, the highest strength was achieved by the E7016 electrode with PWHT 600°C of 940.808 MPa, while the lowest value was shown by the E7018 electrode without PWHT of 572.607 MPa. In the impact test, the highest toughness was obtained by the E7018 electrode with PWHT 600°C of 1.72 J/mm², and the lowest value was found in the E7016 electrode without PWHT of 1.20 J/mm². Thus, PWHT is proven to increase the flexural strength and toughness of the connection, while the electrode selection must be adjusted to the application needs, both for flexural resistance and toughness against dynamic loads..